Analisis Faktor-Faktor yang Mempengaruhi Akuntan Beregister Berprofesi Sebagai Akuntan Publik - Salmiah, Neneng; Afriany, Arista Natia (Akmenika, 2017)
This research aimed at empirically testing of the factors that affect the registeredaccountant as members of IAI in Pekanbaru worked as a public accountant thatfocused to test the effect of the USAP cost, USAP process and occupational riskwith variable electoral career as a public accountant. USAP cost, USAP processand occupational risk variables are as independent variables, associated withvarious assumptions. This research had 45 samples and used purposive sampling asthe technique. Located on Pekanbaru area and using primary data. The datamethod is by spreading some questionnaires. Measurements of variables performedwith Likert scale. Data analysis was conducted through quantitative analysis.Quantitative data analysis was performed by multiple regression analysis andhypothesis testing was done by t-test. The results obtained show that the USAPprocess and occupational risk significantly influence the selection of a career as apublic accountant, USAP cost influence on elections as a public accounting career,but the effect is not significant. Overall USAP cost, USAP process and occupationalrisk jointly significant effect on elections to the selection of a career as a publicaccountant.